Does the Shoe Fit? Real versus Imagined Ecological Footprints - Blomqvist, Linus; Brook, Barry W.; Ellis, Erle C.; Kareiva, Peter M.; Nordhaus, Ted; Shellenberger, Michael (PLOS Biology, 2013)
The global overshoot indicated by Ecological Footprint calculations consists entirely of an unreliable reframing of human carbon emissions and none of the five other land-use categories—cropland, grazing land, built-up land, fishing grounds, and forests. The Ecological Footprint is therefore “so misleading as to preclude its use in any serious science or policy context,” argue Blomqvist et al. in this perspective.